2008
DOI: 10.1111/j.1540-8175.2008.00758.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Left Atrial Appendage by Transesophageal and Combined Two‐ and Three‐Dimensional Transthoracic Echocardiography

Abstract: Our preliminary study suggests that combined 2DTTE and 3DTTE has comparable accuracy to TEE in evaluating the LA and LAA for thrombus. In some patients TEE, but not 3DTTE, may misdiagnose pectinate musculature as thrombus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…Three-dimensional transthoracic echocardiography has shown promise as an imaging modality to assess the LAA. Karakus et al 8 showed that 3D transthoracic echocardiography could detect thrombi and distinguish pectinate muscle from thrombi. However, the image quality of 3D transthoracic echocardiography is generally inferior to that of RT3D TEE, especially for posterior structures such as the LAA, and the broad application of 3D transthoracic echocardiography for assessing thrombi in the LAA may not be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional transthoracic echocardiography has shown promise as an imaging modality to assess the LAA. Karakus et al 8 showed that 3D transthoracic echocardiography could detect thrombi and distinguish pectinate muscle from thrombi. However, the image quality of 3D transthoracic echocardiography is generally inferior to that of RT3D TEE, especially for posterior structures such as the LAA, and the broad application of 3D transthoracic echocardiography for assessing thrombi in the LAA may not be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Because of the close proximity of the transducer to the left ventricular apex, TTE is generally considered to be superior to TEE for thrombus detection. However, TEE has been shown to be a useful complementary approach because of the lack of reflection artifacts and no near-field resolution limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In general, TTE is inferior to TEE in the evaluation of LAA morphology and function [19,27,47]. Poor LAA visualisation in more than 20% patients, inability to identify dysfunction, SEC and blood clots are still major obstacles for use of TTE.…”
Section: Transthoracic Echocardiographymentioning
confidence: 99%